Benchtop fluid visualization in wind tunnel - Tew, Jeffery Wei Xiang (Nanyang Technological University, 2022)
The main objective of this project was to improve the visualization of flows on bodies in a small wind tunnel test section. Flow visualization techniques such as the use of smoke, vapor, and laser sheets were utilized in this experiment because they were primarily used to study flows away from the surface of the model, vortices, and regions of separated flow [1]. It was also a very cost effective method since resources were scarce. The report also included adjusting the parameters of various factors, such as the length of the tubes and the fan speed, to see how this affects the flow. The first and second design concepts were developed by the previous FYP student and were summarized in the next section. They served as the basis for this flow visualization project and as a reference for future design concepts. The third design approach was a top-bottom technique in which the vapor entered the test section from the top. The vapor source was changed from a humidifier to a mist diffuser because the mist diffuser was able to produce much more and clearer smoke than the humidifier. The platform and box were made of plywood to contain the smoke and support the weight of the mist diffuser from top to bottom. Upon examination, it was found that the vapor was heavy, which resulted in the flow not being straight nearing to the end of the test section. Therefore, the use of vapor to represent the flow was not recommended because the results would not be accurate. Also, the flow at the beginning of the test section was considered turbulent. This could be caused by an uneven surface of the wind tunnel before the test section or due to poor connection between the pipe and the tubing. Consequently, further studies were needed to visualize the flow and the causes of turbulent flow. Therefore, the fourth design suggestion was a fog machine. Trial and error were also used to find out the reason for the uneven flow. It was also advisable to use a laser sheet to better visualize the flow. After investigation, it was concluded that a smaller tube made the flow through the bodies better and more visible than a longer tube. In addition, the smaller diameter tube was also more effective at making the flow visible to the naked eye. The respective sections explained step by step how the experiment was conducted, what the results of each design were, and what the possible reasons for the turbulent flow were.